2018
DOI: 10.5530/pj.2018.6s.30
|View full text |Cite
|
Sign up to set email alerts
|

Peels of Citrus Fruits: A Potential Source of Anti-inflammatory and Anti-nociceptive Agents

Abstract: Introduction: The present study was contemplated to evaluate the anti-inflammatory and analgesic potentials in peels of some commercially grown Citrus fruits of South India viz, Lime (Citrus aurantifolia), Orange (Citrus reticulata), Sour Orange (Citrus aurantium), Pomello (Citrus grandis) and Citron (Citrus medica). Methods: The peel of the fruits were separated and subjected to cold extraction using 70% alcohol. The extracts obtained were screened for the presence of phytoconstituents by qualitative phytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Similarly, after 4 h of edema induction, the oral administration (300 and 500 mg/kg BW) of pomelo peels methanol extract determined an inhibition of paw edema by 34.47% and 38.68%, respectively (Ibrahim et al, 2019). The same model of paw was used by Pallavi et al (2018), establishing that intraperitoneal (i.p.) doses (250 and 500 mg/kg) of pomelo peels extract inhibited paw edema (17% and 48%, respectively).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Similarly, after 4 h of edema induction, the oral administration (300 and 500 mg/kg BW) of pomelo peels methanol extract determined an inhibition of paw edema by 34.47% and 38.68%, respectively (Ibrahim et al, 2019). The same model of paw was used by Pallavi et al (2018), establishing that intraperitoneal (i.p.) doses (250 and 500 mg/kg) of pomelo peels extract inhibited paw edema (17% and 48%, respectively).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…[ 17 ] Lemon has been shown to have a pH of 2.21, with additional curative properties such as antibacterial, antiviral, antifungal, anti-inflammatory, and anticancerous activities. [ 18 19 ] The components of lemon juice include ascorbic acid, phenolic acids, polyphenols, and dietary fibers. Different studies have demonstrated lemon’s antimicrobial effectiveness against a wide variety of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested that the mechanism responsible for analgesic and anti-inflammatory activity is due to inhibition of prostaglandin synthesis. Also the presence of flavonoids and their respective aglycones like hesperetin and naringenin might be the reason for the potent anti-inflammatory and analgesic activity [ 10 , 118 120 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%